Nitrogen removal in a Sequencing Batch Biofilm Reactor : effect of carbon availability and intermittent aeration - Vieira, Maria Madalena Costa (2009)
This study aimed to investigate the effects of carbon availability and intermittent aeration on nitrogen removal in a Sequencing Batch Biofilm Reactor (SBBR). The percentage of nitrogen removal in the SBBRs operating with dump fill and slow fill with optimum intermittent aeration was quite similar, 75.7% and 69.2%, respectively, indicating that intermittent aeration allowed a considerable energy saving without compromising significantly nitrogen removal. Accumulation of storage polymers by heterotrophic bacteria was only observed in the dump fill mode of operation. FISH analyses of the biofilm indicated that ammonia-oxidisers belonged to the beta-subclass Proteobacteria and nitrite-oxidisers were affiliated with the genus Nitrospira.